KRIZOVÉ SITUACE A NÁVRH METODIKY REDUKCE DOPRAVNÍ OBSLUHY - Pavel Drdla (Perner’s Contacts, 2006)
The paper deals with the problem of reduction of traffic service in task situation. The result is a design of methodizing for this reduction.